Unraveling the drivers of energy-saving technical change - Diego R. Känzig; Charles Williamson (European Central Bank (ECB), 2024)
We explore the increasing divergence between economic growth and energy consumption through energy-saving technical progress. Proposing a new measure of energy-saving technology, we study the underlying drivers in a semi-structural model of the U.S. economy. Our analysis shows that energy price shocks reduce consumption and stimulate energy-saving innovation, but also cause economic downturns and crowd out other innovations. Only energy-saving technology shocks can explain the negative co-movement between output and energy use. These sudden efficiency gains emerge as the primary driver of energy-saving technical change. Our findings highlight the importance of fostering energy-saving innovations in transitioning to a low-carbon economy.
Keywords: E0; O30; Q32; Q43; Q55; 330; Directed technical change; energy-saving; innovation; energy prices